Phytophthora Species and Their Associations with Chaparral and Oak Woodland Vegetation in Southern California - Sebastian N. Fajardo; Tyler B. Bourret; Susan J. Frankel; David M. Rizzo (Journal of Fungi)
Evidence of unintended introductions of Phytophthora species into native habitats has become increasingly prevalent in California. If not managed adequately, Phytophthora species can become devastating agricultural and forest plant pathogens. Additionally, California’s natural areas, characterized by a Mediterranean climate and dominated by chaparral (evergreen, drought-tolerant shrubs) and oak woodlands, lack sufficient baseline knowledge on Phytophthora biology and ecology, hindering effective management efforts. From 2018 to 2021, soil samples were collected from Angeles National Forest lands (Los Angeles County) with the objective of better understanding the diversity and distribution of Phytophthora species in Southern California. Forty sites were surveyed, and soil samples were taken from plant rhizospheres, riverbeds, and off-road vehicle tracks in chaparral and oak woodland areas. From these surveys, fourteen species of Phytophthora were detected, including P. cactorum (subclade 1a), P. multivora (subclade 2c), P. sp. cadmea (subclade 7a), P. taxon ‘oakpath’ (subclade 8e, first reported in this study), and several clade-6 species, including P. crassamura. Phytophthora species detected in rhizosphere soil were found underneath both symptomatic and asymptomatic plants and were most frequently associated with Salvia mellifera, Quercus agrifolia, and Salix sp. Phytophthora species were present in both chaparral and oak woodland areas and primarily in riparian areas, including detections in off-road tracks, trails, and riverbeds. Although these Mediterranean ecosystems are among the driest and most fire-prone areas in the United States, they harbor a large diversity of Phytophthora species, indicating a potential risk for disease for native Californian vegetation.